Impaired sexual function and prostate cancer: a mixed method investigation into the experiences of men and their partners. Issue 23 (December 2013) - O'Shaughnessy, Peter K; Ireland, Colin; Pelentsov, Lemuel; Thomas, Laws A; Esterman, Adrian J
Abstract : Aims and objectives: To explore issues related to sexual function and relationships, for men and their wives or partners, following diagnosis and treatment for prostate cancer. Background: A diagnosis of prostate cancer and subsequent treatment result in a significant number of men experiencing some impairment to their sexual function. There is scant research into the impact of changed sexual function on these men's masculinity, sexuality, intimate relationships and their needs regarding counselling and supportive care. Design: Internet‐based survey. Methods: Focus groups and couple interviews were used to improve validity for questionnaire items designed to provide insight into men's experiences of prostate cancer in areas such as sexual function and relationships. The questionnaire included both closed and open‐ended questions and had the option for the wife or partner to complete a section. Results: Qualitative research revealed 17 specific categories within three key themes: sexual dysfunction, loss of libido and masculinity. The questionnaire found, unexpectedly, the majority of men said that they had sufficient emotional and psychological support. Wives/partners confirmed cancer had impacted on their partner's feelings of masculinity (71%), compared to 42% of men who felt that this was the case. Predictors of loss of libido, erectile dysfunction and 'feeling less of a man' were developed. Univariate predictors included hormone therapy, regrets about treatment choice, cancer having impacted on masculinity and distress during the last week. Conclusions: Men are not able to clearly identify the challenges prostate cancer brings especially changes to their masculinity. Relevance to clinical practice: The findings strongly suggest that for men with prostate cancer, nursing assessments of men's sexual health be augmented by information gained from their partners; further, these assessments should be augmented with a careful exploration of these men's psyche guided by the knowledge that masculinity influences perceptions of self (being a man) and help seeking.